Integrating Management, Research, and Monitoring: Balancing the 3-Legged Stool - Michael J. Conroy; James T. Peterson (National Quail Symposium Proceedings, 2017)
Research and monitoring programs are often thought of as competing with “on the ground management” for attention and funding. This is false trichotomy; instead, it is more appropriate to view management, research, and monitoring as complementary endeavors, in which loss of any 1 of the 3 is disruptive to the remaining 2. There is often significant or even profound uncertainty about the system’s likely response to management, beyond environmental and other sources of uncontrolled variation. Sometimes this uncertainty can be reduced through directed research studies, including experimentation. However, management decisions usually cannot await the completion of elaborate, multiple-year studies. Adaptive resource management (ARM) provides managers a way to make optimal decisions with respect to resource objectives, given the current level of uncertainty about system response, and in anticipation that learning will improve decision-making through time. Under ARM, resource goals and objectives are always paramount and research and monitoring programs exist to provide managers with the tools they need to make better decisions. The essentials of ARM are clear, compelling, and critically needed in natural resource management. We can no longer afford the luxury, if we ever could, of management divorced from research and monitoring, and vice versa. By keeping the focus on management decision-making and resource objective outcomes, ARM places an explicit value on research and monitoring that then can be used to justify monitoring and research programs.
Keywords: adaptive resource management; decision making; research and monitoring